Analysis of the Costs of Fish Farming in Floating Cages: The Model of Lake 16 Tishreen - الجندي , هلا; غسان يعقوب ,; علي عثمان , (Latakia University Journal -Biological Sciences Series, 2025)
This study targeted the production cost function for freshwater fish farming projects with the aim of estimating the optimal output, the maximum profit output, and the supply function and elasticity of freshwater fish in Lattakia Governorate. It relied on econometric analysis and this study resulted in a set of results, the most important of which are: - Total production costs amounted to about 52.6 million SYP/setof cage. - The current production level reached about 153 tons/cage, and the value of both marginal costs and average total costs reached 11.8,16.8 Million S.P about each, respectively. - The cost elasticity was 0.71. This means that increasing production by 10% leads to an increase in costs by 7.1%. - The optimal production reached 381.94 ton, which is more than the current average production by about 228.94 ton worth 7.74 Millear Syrian pounds, in light of the average selling price of 33800 Syrian pounds in 2023. -The price elasticity of supply for freshwater fish in Latakia Governorate is relatively weak. This is due to the fact that fish are aquatic organisms whose production cannot be controlled, especially in the short term. This study recommends the necessity of increasing the production of freshwater fish farming projects until they move to the stage of economic production.